PENERAPAN ANALISIS WEIBULL PADA PERAWATAN KOMPONEN PESAWAT TERBANG - Dahlan, Dahmir; Pasaribu, Ramlan; Zein, Syahril (MESIN, 2006)
The flight security and reliability the most important issues for the commercialflight company at themoment, to give the scure and competitive services. One of the important factor in this relation is themaintenance system of the part of the airplane it self. The research was conducted that aim the failurecharacteristic ofthe airplane part use the stayiscal Weibull distribution method The location or research isat Garuda Maintenance Facility, in Soekarno-Hatta airport, and take thefailure data ofheat exchanger as asample. The research concluded that, thefailure characteristic Pless than on eis indicated that thefailure isin the beginning ofpart usage. Therefore, continuing research should be conducted tofind the specificfactorthat influenceresult